DEVELOPMENT OF MADRASAH DINIYAH BOARDING SCHOOL AND DINIYYAH EDUCATION: CHANGE OF NOMENCLATURE OF MADRASAH DINIYAH TO FORMAL ELEMENTARY DINIYAH EDUCATION, WUSTHO, ULYA - Halid, Ahmad; bin Jali, Hasan (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2025)
This article examines the development of Islamic boarding school madrasah diniyah into formal Islamic education (PDF). This study uses a qualitative approach by collecting research data through library methods, interviews, documentation, and observation. The results of the study show that Islamic boarding school madrasah is a form of madrasah that only teaches religious knowledge (diniyah). This madrasah is intended as a religious education institution provided for students studying in public schools. However, in its development, Islamic boarding school madrasah has an existence that is recognized as part of the national education system, even in Law Number 20 of 2003 concerning the National Education System in 2014 and in Government Regulation (PP) Number 55 of 2007 concerning Religious Education and Religious Education and reinforced by the decision of the Minister of Religion Number 13 of 2014 concerning Islamic Religious Education, stating that Formal Islamic Boarding School Education (PDF Ulya, Ustho, Ma'had Aly) has an equal position with other formal education. The decision of the Minister of Religion was the beginning of Islamic boarding school madrasah diniyah being able to develop well